Re-thinking ‘Spheres of Responsibility’: Business Responsibility for Indirect Harm - Macdonald, Kate (2011)
This article considers two prominent, competing approaches to defining the scope of business responsibility for human rights. The first approach advocates extension of business responsibility beyond the boundaries of the enterprise to encompass broader ‘spheres of influence’. The second approach advocates a business ‘responsibility to respect’ human rights (but not a ‘positive’ duty to protect, promote or fulfil rights). Building on a critical evaluation of these competing accounts of business responsibility, this article outlines a modified account, referred to as a framework of ‘spheres of responsibility’. On such an account, business responsibility for human rights outcomes is conceptualised not only in relation to direct ‘harms’ imposed by business, but also in relation to corporate influence over broader relationships and institutions that shape and constrain the substantive realisation of human rights.
Keywords: Spheres of influence; responsibility to respect; negative versus positive duties; Corporate Responsibility; business and human rights